PENINGKATAN KOMPETENSI GURU MELALUI PENERAPAN SISTEM DAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN GURU PADA ERA DIGITAL - Maulida, Rizky; Minnah, Ariny Tamamul; Zuhriyah, Indah Aminatuz; Baharuddin, Baharuddin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
Improving the quality of education is closely linked to the development of teacher competence and professionalism, especially in facing the challenges of the digital era. This study aims to explore the implementation of a performance appraisal system and a continuous professional development (CPD) program at Madrasah Ibtidaiyah Maslakul Huda Lamongan as a strategy to enhance teacher competence. A qualitative approach was employed, using data collection techniques such as observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Method triangulation was applied to ensure data validity. The results indicate that the performance appraisal system at MI Maslakul Huda is systematically designed, focusing on four core competencies: pedagogical, personal, social, and professional. This appraisal motivates teachers to enhance their capacity, particularly in the use of technology. The CPD program includes training, both internal and external supervision, and dissemination of training outcomes. The school has provided digital infrastructure and technology training, including artificial intelligence (AI). However, challenges such as digital competence gaps remain. Institutional support through continuous supervision and incentives has proven effective in encouraging teachers. The study concludes that a combination of targeted performance appraisal and relevant CPD is an effective strategy to improve teaching quality in the digital era.